BAP1 mutations inhibit the NF-κB signaling pathway to induce an immunosuppressive microenvironment in uveal melanoma - Chao Zhang; Shuai Wu (BMC, 2023)
Abstract Background Tumor immune microenvironment regulates the growth and metastasis of uveal melanoma (UM). This study aims to reveal the possible molecular mechanism of BRCA1-associated protein 1 (BAP1) mutations in affecting the tumor immune microenvironment in UM through mediating the nuclear factor-κB (NF-κB) signaling pathway. Methods TCGA and cBioPortal databases jointly analyzed the genes with high mutation frequency in UM samples. Following survival analysis of UM patients, UM samples with BAP1 mutations were subjected to immune cell infiltration analysis. The signaling pathways associated with the mutated genes were screened by GSEA. Subsequently, the differential BAP1 expression was analyzed in the selected UM cell lines with wild type (WT) or mutant type (MUT) BAP1. Results Bioinformatics analysis identified 12 genes mutated in the UM samples, while only BAP1 mutations were related to the prognosis of UM patients. UM patients with BAP1 mutations had higher immune cell infiltration. BAP1 mutations inhibited the NF-κB signaling pathway, suppressing the cytokine secretion and antigen presentation by macrophages. Rescue experiments confirmed that overexpressed NF-κB could reverse the effect of BAP1 mutations on the immunosuppressive microenvironment, thus suppressing the malignant phenotypes of UM cells. Conclusion BAP1 mutations may inhibit the NF-κB signaling pathway, repressing the cytokine secretion and antigen presentation by macrophages, which induces the immunosuppressive microenvironment, enhances the malignant phenotypes of UM cells and ultimately promotes the growth and metastasis of UM.